Analysis of Social Interactions of Vegetable Traders in Koto Baru Market, Tanah Datar District, West Sumatra (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study was to examine and analyze the forms and factors of social interaction that occur in the Koto Baru market. In this study using descriptive qualitative research methods. Data collection techniques through observation, interviews and documentation by determining informants by purposive sampling. The results of this study indicate that there is social interaction in the Koto Baru market is divided into two categories, namely associative and dissociative social interactions. Associative social interaction involves cooperation, assimilation and accommodation between vegetable sellers in the market. Cooperation occurs between traders and traders, traders and customers, traders and carriers of goods, and traders and traders outside the city. Assimilation occurs when traders from different cultures adopt practices and norms that are accepted by the majority group. While accommodation occurs in the settlement of conflicts between traders by the head of the market. Several factors influence the occurrence of social interaction in the Koto Baru market. First, there is imitation between vegetable traders where they imitate each other's ways of selling, prices of goods, and how to attract the attention of buyers. Second, identification is carried out by vegetable traders by placing signs or price tags on the merchandise to make it easier for buyers to know the price. Finally, suggestions are given through a friendly attitude and good communication between vegetable traders, which can influence other buyers and traders.